2019
DOI: 10.3390/ijerph17010219
|View full text |Cite
|
Sign up to set email alerts
|

Temperament and Sense of Coherence: Emotional Intelligence as a Mediator

Abstract: Sense of coherence (SOC) reflects an individual’s capacity and available resources to deal with stressful situations. For some time now studies have revealed that people differ in their experience of SOC; yet, very little is known about how and through which mechanisms a high level of SOC is formed. In order to increase our understanding about the paths to a high SOC in the stage of adulthood, we focused on exploring the role both of temperament, as it has been confirmed as a potential component in the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 65 publications
1
13
0
1
Order By: Relevance
“…The words chosen in these verbalizations aimed at several purposes: Generating a sensation of coherence between the internal dimension (feeling) and the external dimension (acting calmly). The sense of coherence (internal–external), in accordance with temperament and emotional intelligence, seems predictive of the individual’s ability to cope with stressful situations [ 63 ]; Facilitating processes of introspection and decoding of the feelings and emotions of the participants to feed a condition of conscious presence; Promoting processes of identification with the elements of nature, which are in dynamic balance and can offer more effective learning and working models [ 64 ]; Stimulating the transformative activity of any dysfunctional aspects detected [ 65 ]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The words chosen in these verbalizations aimed at several purposes: Generating a sensation of coherence between the internal dimension (feeling) and the external dimension (acting calmly). The sense of coherence (internal–external), in accordance with temperament and emotional intelligence, seems predictive of the individual’s ability to cope with stressful situations [ 63 ]; Facilitating processes of introspection and decoding of the feelings and emotions of the participants to feed a condition of conscious presence; Promoting processes of identification with the elements of nature, which are in dynamic balance and can offer more effective learning and working models [ 64 ]; Stimulating the transformative activity of any dysfunctional aspects detected [ 65 ]. …”
Section: Methodsmentioning
confidence: 99%
“…Generating a sensation of coherence between the internal dimension (feeling) and the external dimension (acting calmly). The sense of coherence (internal–external), in accordance with temperament and emotional intelligence, seems predictive of the individual’s ability to cope with stressful situations [ 63 ];…”
Section: Methodsmentioning
confidence: 99%
“…This study used structural equation modelling, but it is also possible that the daughters’ own SOC caused stress, anxiety, and domestic conflict that affected the mothers’ SOC. Previous studies have revealed that irritable temperament is negatively associated with SOC [ 45 ], and adolescence is a period of conflict and irritability [ 46 ]. Therefore, attention has been directed increasingly toward the role that children’s and adolescents’ ability to regulate their own emotions plays in the development of these difficulties [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The words chosen in these verbalizations aimed at several purposes:  Generating a sensation of coherence between the internal dimension (feeling), and the external dimension (acting calmly). The sense of coherence (internal-external), in accordance with temperament and emotional intelligence, seems predictive of the individual's ability to cope with stressful situations [61];  Facilitating processes of introspection and decoding of the feelings and emotions of the participants, to feed a condition of conscious presence;…”
Section: The Methods Of Conducting the Forest Therapy Sessionsmentioning
confidence: 99%